Peningkatan Literasi Keuangan pada Siswa SMA Melalui Edukasi Keuangan - Muthia, Fida; Novriansa, Agil; Aryanto, Aryanto (Universitas Nusantara PGRI Kediri, 2023)
Financial literacy is a person's understanding and knowledge of financial concepts and risks and the ability to apply their understanding and knowledge in decision making that can improve welfare. A good level of financial literacy can avoid the public from the risk of financial fraud. Moreover, if it is associated with financial inclusion, the high level of financial literacy will result in high financial inclusion which in turn will have an impact on poverty eradication, increased development and financial stability. Therefore, it is important to conduct financial education to improve financial literacy. This community service aims to increase the financial literacy in high school students. The event participants were 32 high school students in Palembang and the activity was carried out by providing information about financial products. During the activity, participants were asked to answer two questionnaires; before and after presentation to assess the level of financial literacy. The results show that, providing financial education can increase financial literacy in students.